Optimisme dan Kontrol Diri dengan Coping Stress pada Mahasiswa S1Bimbingan dan Konseling UNNES - Shabrina, Ghaisany; Sunawan, Sunawan; Anni, Catharina Tri (Department of Guidance and Counseling, UNNES, 2019)
ABSTRACT This research aims to know the relationship between optimism and self control with respect to coping stress academic coping stress in undergraduate student guidance and counseling UNNES. This research is an ex postfacto research with a sample of 157 of the population amounted to 288 students with technique of sampling proportionate stratified random sampling. The scale of coping stress in the adaption of the COPE, the scale of optimism in the adaption of the LOT-R, and the scale of self control in the adaption SCS, the scale used in the collection of data with reliability 0,940, 0,769 and 0,937. As for the analysis techniques using double regression. Results of the study showed that between optimism coping stress have a significant relationship (R= 0,529 f(1,555)= 60,101, p =<0,01) then the relationship between coping stress with self control also has a significant relationship (R= 0,366, f(5,150) = 78,544, p=<0,01). Similarly, between optimism and self control with coping stress also has a significant relationship (R= 0,892, f(2,155)= 289,581, p=<0,01).   Key words: coping stress , optimism, self control.